Reflective thinking skills of engineering students in learning statistics - Funny, Rindu Alriavindra; Ghofur, Muhammad Abdul; Oktiningrum, Wuli; Nuraini, Ni Luh Sakinah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
Reflective thinking is known as assessing what they know, what they need to know, and how they bridge that gap during learning situations. Relating what students knew with what they learn today is not easy, sometimes they forget or just cannot make a connection between it. This study will analyze how the students actively participating in reflective thinking by creating project-based learning on statistics lesson based on design research. Thirty-nine engineering students, in a group of four, were asked to make their own data, analyze and transfer it into a poster to inform the readers about the use of statistics in daily life. This study used the measurement of reflective thinking scales by Kember to analyze students answer through the worksheet and instructional activity. The instructional activity succeeds to reveals students thinking of all four skills; habitual action, understanding, reflection, and critical reflection. Furthermore, it also discovered the misuse of some terms when used in daily life.